Maillard reaction product from bovine plasma proteins as antioxidant on model systems - Fernández, Carina Lorena (2014)
A Maillard Reaction Product (MRP) was obtained by reacting bovine plasma proteins and aldehydes arising from oxidized soybean oil. SDS-PAGE electrophoresis and IR studies were developed. Antioxidant activity was analysed by Reducing Power (RP), Chelating Activity (CA) and Antiradical Activity (AA) determinations, using different concentrations of MRP (0 - 8 mg/ml) and BHA (0.01% w/v) as a reference. Oxidative stability of linoleic acid emulsions with 0; 1% and 3% w/v of MRP and 0.01% w/v of BHA was studied. The presence of carboxylic groups was evidenced from IR spectrum, while electrophoresis showed the appearance of new molecular weight constituents. MRP exhibited high RP and CA, but AA was much lower than BHA (35% vs 96%). Inhibition Percentages of Lipid Oxidation were 94% and 97% for MRP and BHA respectively. Consequently, MRP might be an alternative to the synthetic antioxidant, although further studies should be conducted for its application in food systems.